1999
DOI: 10.1177/000348949910801001
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein a in Rabbit Sinus and Middle Ear Mucosa

Abstract: In the present study, pulmonary surfactant protein A (SP-A) messenger RNA (mRNA) and protein were characterized in adult rabbit middle ear and maxillary sinus. Fifteen adult rabbits were used for the study: 6 with evidence of acute middle ear infections and maxillary sinusitis, 6 with infections that were successfully treated with tetracycline, and 3 that were pathogen-free. We detected SP-A mRNA in maxillary sinus and middle ear tissues by Northern blot analysis and reverse transcriptase-polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
3
33
2
Order By: Relevance
“…Recently, Paananen et al (31) described the expression of surfactant protein (SP) A and SP-D in the epithelial lining of the ET. SP-A has also been detected in the middle ear mucosa (8). These data suggest that innate immune responses might play an important role in the protection of the ET against infection.…”
mentioning
confidence: 71%
“…Recently, Paananen et al (31) described the expression of surfactant protein (SP) A and SP-D in the epithelial lining of the ET. SP-A has also been detected in the middle ear mucosa (8). These data suggest that innate immune responses might play an important role in the protection of the ET against infection.…”
mentioning
confidence: 71%
“…Previous immunohistochemical analyses have revealed that SP-A and SP-D are prominently expressed in type II alveolar pneumocytes [38] and that KL-6 is expressed in type II alveolar pneumocytes and in bronchiolar epithelial and bronchial gland cells [39]. Other studies have detected SP-A also in the bronchiolar, tracheal, sinus and middle ear epithelium [17,40,41,42,43]. This study indicates that sputum levels of SP-A, SP-D and KL-6 were elevated in the induced sputum of COPD patients compared to patients with prolonged cough.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that a phospholipid-rich surface lining is not unique to the lung alveoli suggested that other organs might also express SPs. To date, the expression of SPs has been detected in the gastric and intestinal mucosa (1,7), joints (1), peritoneum (1), pericardium (1,7), skin (12), middle ear (2,11), Eustachian tubes (13,14), and maxillary sinus mucosa (2). In addition, surfactant-like materials have been identified in the tongue papillae and oral epithelium (1).…”
mentioning
confidence: 99%